Resource Reallocation and Innovation : Converting Enterprise Risks into Opportunities - Dutz, Mark A. (World Bank, Washington, DC, 2013)
This paper argues that the increased flow and management of knowledge permitted by knowledge-based capital, supported by appropriate policies, can be an important factor in reducing the decision risk facing enterprises due to uncertainty and imperfect information, helping improve the resilience of development outcomes. Enterprises are conceptualized as information platforms that manage risk through investments in knowledge-based capital and complementary assets, providing them with the knowledge, protection/enabling, insurance, and coping/leveraging abilities to make better decisions in response to shocks. Investments in knowledge-based capital allow enterprises to better convert voluntary but risky reallocation and innovation decisions into productivity and wealth-enhancing opportunities. They can help the enterprise sector as a whole and most people to self-protect and realize better jobs, earnings, and consumption outcomes by adapting to shocks. However, absent appropriate policies, knowledge-based capital can have adverse distributional effects -- including a skewed industrial concentration of productivity gains and more unequal consumption and income-earning outcomes between rich and poor people. The paper discusses the role of policy in facilitating risk management by enterprises, ultimately to reduce poverty and boost shared prosperity. Insufficient enterprise risk-taking is costly for the enterprise sector and the economy as it results in too little experimentation and learning. The paper argues that governments should create business environments that stimulate entrepreneurial risk-taking to invest in market and social opportunities that combine new technologies with appropriately-skilled workers. Policies allowing people to better confront and manage their risks include: (1) spurring entrepreneurial experimentation; (2) supporting skills upgrading; and (3) promoting mechanisms for joint learning through global collaboration.